Internalisasi Religius dalam Kompetensi Guru Agama Islam - Hafiedh Hasan (Madaniyah, 2017)
One of the characteristics of a devoted man is to actively carry out and practice Islamic values in his life. Religious Teachers not only provide students with knowledge of religion / knowledge inteklektual, but also trying to shape the mind and the spirit of religion, so that students make/practice what has been taught that in the end become a pious person and have a strong aqeedah. Teacher's personality is used as a benchmark for the success or failure of Islamic Religious Education. Another thing that is also very important to have by the teacher, namely that a teacher must be professional in their field. This has been exemplified by a successful educator figure in a short time, namely Muhammad s.a.w. His success as an educator is based on the provision of high-quality personalities and his concern for social-religious issues. Then he is able to maintain the quality of Faith, charity shaleh, struggling and cooperate to uphold the truth and able to work together in patience. Thus a teacher to be able to perform its role well, always associated with religious values and competencies.